Reply to Comment on 'validity of Feynman's prescription of disregarding the Pauli principle in intermediate states' - Coutinho, FAB; Nogami, Y.; Tomio, L. (American Physical Soc, 2000)
In a recent paper, we raised a question on the validity of Feynman's prescription of disregarding the Pauli principle in intermediate states of perturbation theory. In the preceding Comment, Cavalcanti correctly pointed out that Feynman's prescription is consistent with the exact solution of the model that we used. This means that the Pauli principle does not necessarily apply to intermediate states. We discuss implications of this puzzling aspect.